The Clinical Implication of Vitamin D Nanomedicine for Peritoneal Dialysis-Related Peritoneal Damage - Lee, Yi-Che (Int J Nanomedicine, 2019)
PURPOSE: Vitamin D is a novel potential therapeutic agent for peritoneal dialysis (PD)-related peritoneal fibrosis, but it can induce hypercalcemia and vascular calcification, which limits its applicability. In this study, we create nanotechnology-based drug delivery systems to investigate its therapeutics and side effects. MATERIALS AND METHODS: 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N- [amino-(polyethylene glycol)2000] (DSPE-PEG) and L-α-phosphatidylcholine (PC), which packages with 1α,25(OH)(2)D(3), were used to construct vitamin D nanoliposomes. To confirm the function and safety of vitamin D nanoliposomes, peritoneal mesothelial cells were treated with TGF-β1 and the reverse was attempted using vitamin D nanoliposomes. Antibodies (Ab) against the peritoneum-glycoprotein M6A (GPM6A) Ab were conjugated with vitamin D nanoliposomes. These particles were implanted into mice by intraperitoneal injection and the animals were monitored for the distribution and side effects induced by vitamin D. RESULTS: Vitamin D nanoliposomes were taken up by the mesothelial cells over time without cell toxicity and it also provided the same therapeutic effect in vitro. In vivo study, fluorescent imaging showed vitamin D nanoliposomes allow specific peritoneum target effect and also ameliorate vitamin D side effect. CONCLUSION: Nanoliposomes vitamin D delivery systems for the prevention of PD-related peritoneal damage may be a potential clinical strategy in the future.